Exosomal miR-24-3p mediates myoblast-macrophage crosstalk to promote abdominal muscle repair - Liu, Yuchen; Zou, Zhenyu; Cao, Jinxin; Zhu, Tong; Zhu, Yilin; Shen, Yingmo (Frontiers in Pharmacology, 2025)
ObjectiveThe objective of this study was to explore the role of exosomal miR-24-3p in facilitating communication between myoblasts and macrophages, and to assess its potential in promoting abdominal muscle repair.MethodsWe utilized C2C12 myoblasts and RAW 264.7 macrophages, inducing the latter into an M2 phenotype. miR-24-3p levels were manipulated via transfection, and exosomes were isolated from M2 macrophages using ultracentrifugation. Exosome characterization was performed using TEM and Western blot. In vitro assays evaluated C2C12 cell proliferation, migration, and differentiation. In vivo, a cardiotoxin-induced mouse model of muscle injury was used to assess the effects of exosomal miR-24-3p on muscle repair, including histological assessment and analysis of cytokine and metabolic markers.ResultsOur results demonstrated that exosomal miR-24-3p, when isolated from M2 macrophages, was effectively internalized by C2C12 cells and significantly enhanced their metabolic activity, proliferation, and migratory capabilities. Moreover, it induced cellular differentiation, as observed under microscopic examination. In the abdominal muscle injury model, the administration of exosomal miR-24-3p led to a reduction in muscle fiber damage, fibrosis, and inflammation. It also promoted the restoration of glucose and lipid metabolism, which is critical for the energy demands of regenerating muscle. Furthermore, exosomal miR-24-3p upregulated the expression of genes associated with muscle cell proliferation and differentiation, suggesting its potential role in muscle repair.ConclusionIn conclusion, exosomal miR-24-3p plays a significant role in facilitating abdominal muscle repair by mediating the interaction between myoblasts and macrophages.